Beekeeping, agroecosystems and africanization of Apis mellifera diagnosis, in Comalcalco, Tabasco, Mexico - Gómez-Leyva, Juan Florencio; May-Esquivel, Fernando; Vázquez-Hernández, Lorena; Gallegos-González, Miriam; Catzím-Rojas, Francisco Javier; Payro-De la Cruz, Emeterio (Ecosistemas y Recursos Agropecuarios, 2022)
Beekeeping generates currencies for Mexico, however, Tabasco ranks 25th in national production. The municipality of Comalcalco has agroecological resources with beekeeping potential. In order to analyze the socioeconomic and technical aspects of beekeeping, 11 beekeepers were interviewed, classifying them into four strata. The apiaries were georeferenced for geoprocessing. Africanization was determined by mtDNA in drones. The average age of the beekeepers was 48 years, with 8 years of experience, detecting that beekeeping is not their main economic activity. Honey yield was 46.2 kg Colony−1 higher than the state average (37 kg Colony−1). The mtDNA analysis identified 100% Africanization, possibly due to the fact that the annual replacement of queen bees of European origin does not take place. Four contrasting agroecosystems were identified. The results found indicate that it is necessary to implement strategies for the sustainable use of beekeeping and generational germplasm in the entity.